Structural and functional analyses of biosimilar enoxaparins available in Brazil - Oliveira, Stephan-Nicollas M. C. G.; Santos, Gustavo R. C.; Glauser, Bianca F.; Capillé, Nina V. M.; Queiroz, Ismael N. L.; Pereira, Mariana S.; Pomin, Vitor H.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2015)
Biosimilar enoxaparins have been available for clinical use in Brazil since 2009. Although their use has reduced costs of treatment expenses, their implementation still raises some concerns about efficiency, safety, regularity and reproducibility of batches. We undertook structural and functional analyses on over 90 batches of pharmaceutical- active ingredient, and 330 ones of the final products of biosimilar enoxaparins available in the Brazilian market between 2009 and 2014. Besides a nationwide-scale analysis, we have also employed methods that go beyond those recommended by the standard pharmacopeias. We have used high-resolution 2D NMR, detailed assessment of the anticoagulant and antithrombotic properties, check of side effects in experimental animals after continuous administration, and analyses of individual composing oligosaccharides. The 1D 1H NMR spectra of all batches of biosimilar enoxaparins are fairly coincident, and the resultant average spectrum is quite identical to that from the original drug. This structural equality was also assured by highly resolved 2D NMR spectra. The anticoagulant activity, determined by diverse assays and the in vivoantithrombotic and bleeding effects of the biosimilar version were confirmed as equal as of the parental enoxaparins. Structure and function of the composing oligosaccharides were identical in both enoxaparin types. No side effect was observed after continuous subcutaneous administration to rats for 30 days at the dose of 2 mg kg-1 body weight. Biosimilar enoxaparins available in Brazil fulfilled the requirement of the five items defined by FDA-USA for approval of this type of drug.
Keywords: Heparins; thrombosis; animal models; pharmacovigilance of heparin; low-molecular-weight heparin